Risk Analysis of Occupational Health and Safety in the Use of Gas Chromatography-Flame Ionisation Detector Using the House of Risk Safety, Health, Etc Method - Shafa Amalia Insani; Adithya Sudiarno (Journal of Social Research, 2026)
This study aims to analyze and evaluate occupational safety and health (OSH) risks associated with the use of Gas Chromatography-Flame Ionisation Detection (GC-FID) equipment at PT. XYZ's laboratory. The GC-FID tool combines gas chromatography for compound separation and flame ionisation detection for measuring organic compound concentrations. It plays a crucial role in maintaining product quality before cigarettes are packaged. The study identifies and maps potential hazards in three operational stages: startup, operation, and shutdown. Risks such as gas leaks, flammable gas leaks, and burns due to high temperatures (150–200 °C) were found. Currently, the OSH management relies on standard operating procedures and personal protective equipment (PPE) without a structured system in place. Using the Healthy, Etc (HORshe) risk analysis method, the study identified 10 risk events and 11 risk agents. Through this analysis, 13 preventive measures were developed to mitigate the identified risks. The expected outcome is to improve OSH management, reduce workplace accidents, and create a safer and healthier working environment. The study provides strategic recommendations to enhance OSH practices in the laboratory.